2005
DOI: 10.1097/01.alc.0000171934.22755.6d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corpus Callosum Anisotropy in Young Adults With Fetal Alcohol Syndrome According to Diffusion Tensor Imaging

Abstract: Our results illustrate that DTI can be used in evaluating the integrity of corpus callosum in alcohol-exposed individuals. If future studies support these findings, diffusion anisotropy, represented by fractional anisotropy, has the potential to be used as a clinical marker in the diagnosis of FAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
106
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 38 publications
21
106
6
Order By: Relevance
“…3d, e, our VBM result also shows decreased WM in the corpus callosum and increased GM at least in the ventral frontal lobe and bilateral parietal areas. These observations are all consistent with the previous findings reported by morphological studies of PAE (Archibald et al 2001;Ma et al 2005;Sowell et al 2001a;Sowell et al 2001b;Sowell et al 2002). As generally described by Sowell and colleagues (2001b), the PAE subjects tend to have too much gray matter and too little white matter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3d, e, our VBM result also shows decreased WM in the corpus callosum and increased GM at least in the ventral frontal lobe and bilateral parietal areas. These observations are all consistent with the previous findings reported by morphological studies of PAE (Archibald et al 2001;Ma et al 2005;Sowell et al 2001a;Sowell et al 2001b;Sowell et al 2002). As generally described by Sowell and colleagues (2001b), the PAE subjects tend to have too much gray matter and too little white matter.…”
Section: Discussionsupporting
confidence: 92%
“…(Archibald et al 2001;Riikonen et al 1999;Sowell et al 2001b;Sowell et al 2002). By using the diffusion tensor imaging (DTI) technique, we recently also found significant difference in the diffusion fractional anisotropy and apparent diffusion coefficient in the corpus callosum of alcohol-affected young adults compared with the non-exposed controls (Ma et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Consistent with sMRI-revealed abnormal midline structures, a number of DTI studies have reported decreased FA in the corpus callosum of children and young adults with FASD, both as a whole structure [70] and in different subregions including the splenium, posterior mid-body and isthmus [71][72][73][74]. Children and young adults with FASD also exhibited lower FA in the right cingulum, bilateral inferior and superior longitudinal fasciculi (ILF and SLF respectively) and left thalamus [74][75][76]; the frontal, parietal and occipital lobes [73;77]; the medial prefrontal cortex and posterior cingulate cortex [78];…”
supporting
confidence: 56%
“…Recently, diffusion tensor imaging (DTI) was used to evaluate the white matter integrity of the corpus callosum in alcohol-exposed participants (Ma et al, 2005). Diffusion tensor imaging (DTI) makes use of the random properties of water diffusion to generate images that can be used to evaluate tissue microstructure.…”
Section: Corpus Callosummentioning
confidence: 99%